Environment-friendly solar photovoltaic cable material and preparation method thereof

By using modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone in solar photovoltaic cable materials, combined with modified straw ash and nano calcium carbonate powder, the problem of smoke and toxic gas release during cable combustion is solved, and the efficient flame retardant and heat resistance of the cable is improved.

CN119931188APending Publication Date: 2025-05-06GUANGDONG JINYUANYU WIRE & CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510039992.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-05-06

AI Technical Summary

Technical Problem

Existing solar photovoltaic cable materials release a large amount of smoke and toxic gases when burning, which poses a major safety hazard and has uneven flame retardant effects.

Method used

The environmentally friendly solar photovoltaic cable material including ethylene-vinyl acetate copolymer, polyethylene, modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone resin is used to improve the flame retardancy and heat resistance of the cable by adding modified straw ash and nano calcium carbonate powder.

Benefits of technology

It significantly improves the flame retardant performance and heat resistance of the cable, reduces the release of smoke and toxic gases during combustion, and enhances the safety of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119931188A_ABST
    Figure CN119931188A_ABST
Patent Text Reader

Abstract

The invention provides an environment-friendly solar photovoltaic cable material and a preparation method thereof. The environment-friendly solar photovoltaic cable material comprises 65-75 parts of an ethylene-vinyl acetate copolymer, 40-60 parts of polyethylene, 15-20 parts of a flame retardant, 10-15 parts of nano calcium carbonate powder, 1-2 parts of a silane coupling agent, 2-5 parts of titanate, 1-5 parts of modified straw ash, 3-10 parts of zinc oxide and 4-5 parts of dialkane peroxide. Wherein the flame retardant is prepared from modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicon resin; wherein the modified straw ash is obtained by modifying straw ash through glass beads, sodium lauryl sulfate, polyethylene glycol and magnesium hydroxide. The modified magnesium hydroxide, the ATC-DOPO, the melamine cyanurate and the methyl MQ silicon resin are used as flame retardants, so that the flame retardance of the cable is improved; the straw ash is modified, so that the flame retardance and heat resistance of the cable are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of charging cables, and in particular to an environmentally friendly solar photovoltaic cable material and a preparation method thereof. Background Art

[0002] A solar photovoltaic system is a device that converts solar energy into electrical energy. It converts sunlight directly into direct current through solar panels, which can then be converted into alternating current through an inverter and supplied to homes, businesses or power grids. It is mainly composed of solar panels, inverters, battery storage systems, distribution boxes, cables and connectors, brackets and mounting structures, of which the cables are mainly environmentally friendly cables.

[0003] However, with the frequent occurrence of electrical fire accidents, the flame retardancy of cables has gradually attracted the attention of countries around the world. When cables burn, they release a lot of smoke and toxic and corrosive gases, which are dangerous factors in fires. They hinder people's safe evacuation and fire fighting, causing serious losses of life and property. Therefore, it is of great significance to improve the flame retardancy and environmental protection of solar photovoltaic cable materials. Summary of the invention

[0004] In view of the above problems, the present application is proposed to provide an environmentally friendly solar photovoltaic cable material and a preparation method thereof that overcomes the above problems or at least partially solves the above problems, comprising:

[0005] An environmentally friendly solar photovoltaic cable material is used to prepare a cable sheath, and comprises the following components by weight:

[0006] 65-75 parts of ethylene-vinyl acetate copolymer, 40-60 parts of polyethylene, 15-20 parts of flame retardant, 10-15 parts of nano calcium carbonate powder, 1-2 parts of silane coupling agent, 2-5 parts of titanate, 1-5 parts of modified straw ash, 3-10 parts of zinc oxide, 4-5 parts of dialkyl peroxide;

[0007] Wherein, the flame retardant includes modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone resin;

[0008] The modified straw ash is prepared by modifying the straw ash with vitrified microspheres, sodium lauryl sulfate, polyethylene glycol and magnesium hydroxide.

[0009] Furthermore, the mass ratio of the modified magnesium hydroxide, the ATC-DOPO, the melamine cyanurate and the methyl MQ silicone resin is 14:7:24:55.

[0010] Furthermore, the modified magnesium hydroxide is prepared by surface-modifying the magnesium hydroxide using a silane coupling agent and a titanate.

[0011] Furthermore, the polyethylene is linear low-density polyethylene, ultra-low-density polyethylene or high-density polyethylene.

[0012] Furthermore, the modified straw ash is prepared by the following method:

[0013] adding a cleaning agent to the straw ash to remove impurities;

[0014] 2-3% of vitrified microspheres, 2-3% of sodium lauryl sulfate, 1-2% of polyethylene glycol and 3-5% of magnesium hydroxide are added to the straw ash, and the mixture is stirred at high speed, dried and crushed to obtain the modified straw ash.

[0015] Furthermore, the modified magnesium hydroxide is prepared by the following method:

[0016] The silane coupling agent and the titanate are respectively added into anhydrous ethanol to obtain a mixed solution;

[0017] Magnesium hydroxide is added to the mixed solution, and dried at a specified temperature for a specified time to obtain the modified magnesium hydroxide.

[0018] Furthermore, based on weight, the invention also includes 1-3 parts of lubricant and 0.1-2 parts of antioxidant.

[0019] Furthermore, the lubricant is at least one of stearic acid, zinc stearate, castor oil, polyethylene wax, paraffin and white oil.

[0020] Furthermore, the antioxidant is at least one of antioxidant 1010 and antioxidant 168 .

[0021] A method for preparing the environmentally friendly solar photovoltaic cable as described above comprises the steps of:

[0022] Weighing each raw material according to its weight, and evenly mixing ethylene-vinyl acetate copolymer, polyethylene and nano calcium carbonate powder to obtain a first mixed raw material;

[0023] Adding a flame retardant, a silane coupling agent, a titanate, modified straw ash, zinc oxide and dialkyl peroxide to the first mixed raw material in parts by weight to obtain a second mixed raw material;

[0024] The second mixed raw material is mixed and granulated to obtain the target environmentally friendly solar photovoltaic cable material.

[0025] This application has the following advantages:

[0026] In the embodiments of the present application, with respect to the problem in the prior art that cables release a large amount of smoke and toxic and corrosive gases when burning, the present application provides a solution for improving the flame retardancy of cables by adding new flame retardants and improving straw ash, specifically: the following components are included by weight: 65-75 parts of ethylene-vinyl acetate copolymer, 40-60 parts of polyethylene, 15-20 parts of flame retardant, 10-15 parts of nano calcium carbonate powder, 1-2 parts of silane coupling agent, 2-5 parts of titanate, 1-5 parts of modified straw ash, 3-10 parts of zinc oxide, and 4-5 parts of dialkyl peroxide; wherein the flame retardant includes modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone resin; wherein the modified straw ash is obtained by modifying straw ash with glass microspheres, sodium lauryl sulfate, polyethylene glycol and magnesium hydroxide. The flame retardancy of the cable is improved by using modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone resin as flame retardants; the flame retardancy and heat resistance of the cable are improved by modifying the straw ash. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the description of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0028] Figure 1 It is a schematic flow chart of a method for preparing an environmentally friendly solar photovoltaic cable provided in one embodiment of the present application. DETAILED DESCRIPTION

[0029] In order to make the objects, features and advantages of the present application more obvious and understandable, the present application is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0030] The inventors analyzed the prior art and found that the flame retardants used in existing solar photovoltaic cable materials have poor dispersibility and uneven flame retardant effects. The flames can easily spread on the surface of the cable material, causing a large amount of smoke to be released when the cable burns, posing certain safety hazards.

[0031] Reference Figure 1 , shows an environmentally friendly solar photovoltaic cable provided by an embodiment of the present application, which is used to prepare a cable sheath and includes the following components by weight:

[0032] 65-75 parts of ethylene-vinyl acetate copolymer, 40-60 parts of polyethylene, 15-20 parts of flame retardant, 10-15 parts of nano calcium carbonate powder, 1-2 parts of silane coupling agent, 2-5 parts of titanate, 1-5 parts of modified straw ash, 3-10 parts of zinc oxide, 4-5 parts of dialkyl peroxide;

[0033] Wherein, the flame retardant includes modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone resin;

[0034] The modified straw ash is prepared by modifying the straw ash with vitrified microspheres, sodium lauryl sulfate, polyethylene glycol and magnesium hydroxide.

[0035] In the embodiments of the present application, with respect to the problem in the prior art that cables release a large amount of smoke and toxic and corrosive gases when burning, the present application provides a solution for improving the flame retardancy of cables by adding new flame retardants and improving straw ash, specifically: the following components are included by weight: 65-75 parts of ethylene-vinyl acetate copolymer, 40-60 parts of polyethylene, 15-20 parts of flame retardant, 10-15 parts of nano calcium carbonate powder, 1-2 parts of silane coupling agent, 2-5 parts of titanate, 1-5 parts of modified straw ash, 3-10 parts of zinc oxide, and 4-5 parts of dialkyl peroxide; wherein the flame retardant includes modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone resin; wherein the modified straw ash is obtained by modifying straw ash with glass microspheres, sodium lauryl sulfate, polyethylene glycol and magnesium hydroxide. The flame retardancy of the cable is improved by using modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone resin as flame retardants; the flame retardancy and heat resistance of the cable are improved by modifying the straw ash.

[0036] Next, an environmentally friendly solar photovoltaic cable in this exemplary embodiment will be further described.

[0037] In one embodiment of the present application, the mass ratio of the modified magnesium hydroxide, the ATC-DOPO, the melamine cyanurate and the methyl MQ silicone resin is 14:7:24:55.

[0038] It should be noted that the modified magnesium hydroxide is a magnesium hydroxide surface modified by a silane coupling agent and a titanate. The ATC-DOPO is a P / N (phosphine / nitrogen) bifunctional compound containing a DOPO (9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxide) group and an ATC (triazole ring), wherein the structure of DOPO is as follows:

[0039]

[0040] In one embodiment of the present application, the polyethylene is linear low-density polyethylene, ultra-low-density polyethylene or high-density polyethylene.

[0041] It should be noted that ethylene-vinyl acetate copolymer is blended with linear low-density polyethylene, ultra-low-density polyethylene and high-density polyethylene through a single-screw extruder and granulated to serve as the base resin.

[0042] As an example, the base resin includes ethylene-vinyl acetate copolymer and linear low density polyethylene.

[0043] As another example, the base resin includes ethylene vinyl acetate copolymer and ultra low density polyethylene.

[0044] In one embodiment of the present application, the modified straw ash is prepared by the following method:

[0045] adding a cleaning agent to the straw ash to remove impurities;

[0046] 2-3% of vitrified microspheres, 2-3% of sodium lauryl sulfate, 1-2% of polyethylene glycol and 3-5% of magnesium hydroxide are added to the straw ash, and the mixture is stirred at high speed, dried and crushed to obtain the modified straw ash.

[0047] As an example, the cleaning agent is 10-15% hydrochloric acid, 10-15% hydrochloric acid is added to the straw ash, and after soaking for a period of time, the straw ash is rinsed with deionized water until neutral. The period of time is to ensure that the hydrochloric acid is fully in contact with the straw ash, thereby effectively removing impurities in the ash, preferably 2-4 hours. After drying the straw ash, 2-3% of vitrified microspheres, 2-3% of sodium lauryl sulfate, 1-2% of polyethylene glycol and 3-5% of magnesium hydroxide are added to the straw ash for high-speed stirring, and the modified straw ash is obtained after drying and crushing.

[0048] In one embodiment of the present application, the modified magnesium hydroxide is prepared by the following method:

[0049] The silane coupling agent and the titanate are respectively added into anhydrous ethanol to obtain a mixed solution;

[0050] Magnesium hydroxide is added to the mixed solution, and dried at a specified temperature for a specified time to obtain the modified magnesium hydroxide.

[0051] As an example, the silane coupling agent and the titanate are respectively added to anhydrous ethanol to obtain a mixed solution; wherein the weight ratio of the silane coupling agent, the titanate and anhydrous ethanol is 1.5:1:22.5. Then magnesium hydroxide is added to the mixed solution, and the weight ratio of magnesium hydroxide to anhydrous ethanol is 1:2. Dry at 80-85 degrees Celsius for half a day to obtain the modified magnesium hydroxide. The synergistic use of silane coupling agent and titanate can improve the flame retardancy and tensile strength of cable materials.

[0052] In one embodiment of the present application, the composition further includes 1-3 parts of lubricant and 0.1-2 parts of antioxidant, by weight.

[0053] In one embodiment of the present application, the lubricant is at least one of stearic acid, zinc stearate, castor oil, polyethylene wax, paraffin and white oil.

[0054] In one embodiment of the present application, the antioxidant is at least one of the antioxidant 1010 and the antioxidant 168 .

[0055] Reference Figure 1 The present application also provides a method for preparing an environmentally friendly solar photovoltaic cable, comprising the steps of:

[0056] S1. Weigh each raw material according to its weight, and mix ethylene-vinyl acetate copolymer, polyethylene and nano calcium carbonate powder evenly to obtain a first mixed raw material;

[0057] S2, adding a flame retardant, a silane coupling agent, a titanate, modified straw ash, zinc oxide and dialkyl peroxide to the first mixed raw material in parts by weight to obtain a second mixed raw material;

[0058] S3, mixing and granulating the second mixed raw material to obtain a target environmentally friendly solar photovoltaic cable material.

[0059] Next, a method for preparing an environmentally friendly solar photovoltaic cable in this exemplary embodiment will be further described.

[0060] As described in step S1, each raw material is weighed according to the weight of the constituent raw materials, and ethylene-vinyl acetate copolymer, polyethylene and nano calcium carbonate powder are mixed evenly to obtain a first mixed raw material.

[0061] As an example, 65-75 parts of ethylene-vinyl acetate copolymer, 40-60 parts of polyethylene, and 10-15 parts of nano calcium carbonate powder are weighed, and the weighed components are mixed evenly to obtain a first mixed raw material.

[0062] As described in step S2, a flame retardant, a silane coupling agent, a titanate, modified straw ash, zinc oxide and dialkyl peroxide are added to the first mixed raw material in parts by weight to obtain a second mixed raw material.

[0063] As an example, 15-20 parts of flame retardant, 1-2 parts of silane coupling agent, 2-5 parts of titanate, 1-5 parts of modified straw ash, 3-10 parts of zinc oxide, and 4-5 parts of dialkyl peroxide are weighed, and the weighed components are mixed with the first mixed raw material, and stirred at low speed at room temperature for 1-2 minutes to obtain a second mixed raw material.

[0064] As described in step S3, the second mixed raw material is mixed and granulated to obtain the target environmentally friendly solar photovoltaic cable material.

[0065] As an example, the second mixed raw material is added into a twin-screw extruder for mixing and granulation at 140-170° C. to obtain the target environmentally friendly solar photovoltaic cable material.

[0066] The following are specific examples:

[0067] Example 1

[0068] An environmentally friendly solar photovoltaic cable material comprises the following components by weight:

[0069] 70 parts of ethylene-vinyl acetate copolymer, 50 parts of polyethylene, 15 parts of flame retardant, 10 parts of nano calcium carbonate powder, 2 parts of silane coupling agent KH550, 3 parts of titanate, 5 parts of modified straw ash, 5 parts of zinc oxide, and 5 parts of dialkyl peroxide;

[0070] The flame retardant is modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone resin in a mass ratio of 14:7:24:55;

[0071] The structure of ATC-DOPO is as follows:

[0072]

[0073] A method for preparing an environmentally friendly solar photovoltaic cable material:

[0074] The silane coupling agent, the titanate and anhydrous ethanol are mixed in a ratio of 1.5:1:22.5 to obtain a mixed solution. Magnesium hydroxide is then added to the mixed solution, and the weight ratio of magnesium hydroxide to anhydrous ethanol is 1:2. The mixture is dried at 80-85 degrees Celsius for half a day to obtain modified magnesium hydroxide;

[0075] 10-15% hydrochloric acid is added to the straw ash, and after soaking for 3 hours, the straw ash is rinsed with deionized water until it is neutral. After drying the straw ash, 2-3% of vitrified microspheres, 2-3% of sodium lauryl sulfate, 1-2% of polyethylene glycol and 3-5% of magnesium hydroxide are added to the straw ash, stirred at high speed, dried and crushed to obtain modified straw ash;

[0076] Weighing each raw material according to its weight, and evenly mixing ethylene-vinyl acetate copolymer, polyethylene and nano calcium carbonate powder to obtain a first mixed raw material;

[0077] Adding a flame retardant, a silane coupling agent, a titanate, modified straw ash, zinc oxide and dialkyl peroxide to the first mixed raw material in parts by weight to obtain a second mixed raw material;

[0078] The second mixed raw material is added into a twin-screw extruder for mixing and granulation at 140-170° C. to obtain the target environmentally friendly solar photovoltaic cable material.

[0079] Comparative Example 1

[0080] Compared with Example 1, the only difference is that the flame retardant is magnesium hydroxide.

[0081] Comparative Example 2

[0082] Compared with Example 1, the only difference is that no modified straw ash is added.

[0083] Comparative Example 3

[0084] Compared with Comparative Example 1, the only difference is that no modified straw ash is added.

[0085] The cable materials prepared in Example 1 and Comparative Examples 1 and 2 were subjected to performance tests, wherein the testing methods involved were: the tensile test was conducted in accordance with GB / T1040.3-2006; the elongation at break was conducted in accordance with GB / T1040.3-2006; the oxygen index was conducted in accordance with GB / T 2406.3-2022; the heat deformation temperature was conducted in accordance with GB / T1634; and the smoke density was conducted in accordance with GB / T 8323.2-2008. The specific results are shown in Table 1 below:

[0086] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength(Mpa) 25.7 25.3 23.6 19.4 Elongation at break (%) 327 316 314 305 Oxygen index (%) 35 28 26 24 Heat deformation temperature (1.8Mpa / ℃) 77.5 64.2 61.0 56.6 Smoke density (%) 219 238 231 252

[0087] Table 1

[0088] It can be seen from the test results in Table 1 that the cable material of the present invention has excellent flame retardancy, wear resistance and smoke suppression performance.

[0089] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0090] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present application.

[0091] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or terminal device including the elements.

[0092] The above is a detailed introduction to an environmentally friendly solar photovoltaic cable and a preparation method thereof provided by the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for general technicians in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. An environmentally friendly solar photovoltaic cable material for preparing a cable sheath, characterized in that: The following components are included by weight: 65-75 parts of ethylene-vinyl acetate copolymer, 40-60 parts of polyethylene, 15-20 parts of flame retardant, 10-15 parts of nano calcium carbonate powder, 1-2 parts of silane coupling agent, 2-5 parts of titanate, 1-5 parts of modified straw ash, 3-10 parts of zinc oxide, 4-5 parts of dialkyl peroxide; Wherein, the flame retardant includes modified magnesium hydroxide, ATC-DOPO, melamine cyanurate and methyl MQ silicone resin; The modified straw ash is prepared by modifying the straw ash with vitrified microspheres, sodium lauryl sulfate, polyethylene glycol and magnesium hydroxide.

2. The environmentally friendly solar photovoltaic cable material according to claim 1, characterized in that: The mass ratio of the modified magnesium hydroxide, the ATC-DOPO, the melamine cyanurate and the methyl MQ silicone resin is 14:7:24:

55.

3. The environmentally friendly solar photovoltaic cable material according to claim 1, characterized in that: The modified magnesium hydroxide is prepared by surface-modifying the magnesium hydroxide using a silane coupling agent and a titanate.

4. The environmentally friendly solar photovoltaic cable material according to claim 1, characterized in that: The polyethylene is linear low-density polyethylene, ultra-low-density polyethylene or high-density polyethylene.

5. The environmentally friendly solar photovoltaic cable material according to claim 1, characterized in that: The modified straw ash is prepared by the following method: adding a cleaning agent to the straw ash to remove impurities; 2-3% of vitrified microspheres, 2-3% of sodium lauryl sulfate, 1-2% of polyethylene glycol and 3-5% of magnesium hydroxide are added to the straw ash, and the mixture is stirred at high speed, dried and crushed to obtain the modified straw ash.

6. The environmentally friendly solar photovoltaic cable material according to claim 3, characterized in that: The modified magnesium hydroxide is prepared by the following method: The silane coupling agent and the titanate are respectively added into anhydrous ethanol to obtain a mixed solution; Magnesium hydroxide is added to the mixed solution, and dried at a specified temperature for a specified time to obtain the modified magnesium hydroxide.

7. The environmentally friendly solar photovoltaic cable material according to claim 1, characterized in that: By weight, the invention also includes 1-3 parts of lubricant and 0.1-2 parts of antioxidant.

8. The environmentally friendly solar photovoltaic cable material according to claim 7, characterized in that: The lubricant is at least one of stearic acid, zinc stearate, castor oil, polyethylene wax, paraffin and white oil.

9. The environmentally friendly solar photovoltaic cable material according to claim 7, characterized in that: The antioxidant is at least one of the antioxidant 1010 and the antioxidant 168 .

10. A method for preparing an environmentally friendly solar photovoltaic cable material, characterized in that: Includes steps: Weighing each raw material according to its weight, and evenly mixing ethylene-vinyl acetate copolymer, polyethylene and nano calcium carbonate powder to obtain a first mixed raw material; Adding a flame retardant, a silane coupling agent, a titanate, modified straw ash, zinc oxide and dialkyl peroxide to the first mixed raw material in parts by weight to obtain a second mixed raw material; The second mixed raw material is mixed and granulated to obtain the target environmentally friendly solar photovoltaic cable material.